Simulation Analysis of Face Gear Roll Forming - Guang Zhang; Fengshou Zhang; Yuanyuan Jin; Li Li (Jixie chuandong)
Based on the roll deformation theory，a roll model through Deform-3D finite element simulation software is established，the roll forming process of the face gear is analyzed and the metal flow conditions of the active and passive faces of the face gear tooth profile is analyzed according to the finite element simulation results； the influence trend of process parameters on the maximum load of the rolling wheel and the distribution law of equivalent strain and equivalent residual stress on the tooth profile are analyzed. The results show that， the metal fluidity of the passive surface of the tooth profile of the face gear is greater than that of the active surface，and “lugs” are easily formed on the tooth top of the passive surface； the maximum load of the rolling wheel decreases with the increase of the speed，and the feed speed increases. The maximum load of the rolling wheel increases； the change trend of the equivalent strain of the tooth profile and the maximum residual stress is the same，which increases with the increase of the speed，and decreases with the increase of the feed speed. These results provide certain reference significance for further experiments.